Staf Pengajar Fakultas Ekonomi dan Pascasarjana Universitas 17 Agustus 1945 Surabaya - Istiono, * (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2010)
This research was done to see the effects of company risk to profitability and value of a firm. The results of analysis show that: the company risk did not have a significant effect on profitability; the company risk did not have a significant effect on value of a firm; profitability had a significant effect on value of the firm; and both company risk and profitability simultaneously had a significant effect on value of a firm.Keywords: company risk, profitability, and value of a firm.